THE EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND GROWTH ON DIVIDEND POLICY IN FOOD AND BEVERAGE COMPANIES THAT LISTED ON INDONESIA STOCK EXCHANGE - Dian Fitri Handayani; Nurma Gupita Dewi (SEAN Institute, 2023)
This study aims to analyze the effect of Current Ratio, Debt To Equity Ratio and Growth on Dividend Policy in Food and Beverage Companies Listed on the Indonesia Stock Exchange. The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 period. The sampling technique in this study used purposive sampling , namely the technique of determining the sample with certain criteria. The data used in this study are secondary data, through intermediary media obtained from the Indonesia Stock Exchange (IDX) in the form of financial statements of companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The results showed that CR had no significant negative effect on dividend policy , DER had no significant positive effect on dividend policy and growth bet had a significant positive effect on dividend policy in food and beverage companies listed on the Indonesia Stock Exchange (IDX) .